Drug-related problems among transfusion-dependent thalassemia patients: A real-world evidence study - Chun, Geok Ying; Mohd Tahir, Nurul Ain; Islahudin, Farida; Selvaratnam, Veena; Li, Shu Chuen (Frontiers in Pharmacology, 2023)
Introduction: Thalassemia is among the most common genetic disorders globally and many patients suffer from iron overload (IOL) complications that mainly affect the heart, liver and endocrine system. These events may be further complicated by drug-related problems (DRP), an inherent issue among patients with chronic diseases. Objective: The study aimed to evaluate the burden, associated factors and impacts of DRP in transfusion-dependent thalassemia (TDT) patients. Method: Eligible TDT patients under follow-up in a tertiary hospital between 01 March 2020 to 30 April 2021 were interviewed and their medical records were reviewed retrospectively to identify any DRP. DRPs were classified using the Pharmaceutical Care Network Europe (PCNE) classification version 9.1. The incidence and preventability of DRP were assessed and the associated risk factors were estimated by univariate and multivariate logistic regression. Results: A total of 200 patients were enrolled with a median (interquartile range: IQR) age of 28 years at enrolment. Approximately 1 in 2 patients were observed to suffer from thalassemia-related complications. Throughout the study period, 308 DRPs were identified among 150 (75%) participants, with a median DRP per participant of 2.0 (IQR 1.0–3.0). Of the three DRP dimensions, treatment effectiveness was the most common DRP (55.8%) followed by treatment safety (39.6%) and other DRP (4.6%). The median serum ferritin level was statistically higher in patients with DRP compared with patients without DRP (3833.02 vs. 1104.98 μg/L, p < 0.001). Three risk factors were found to be significantly associated with the presence of DRP. Patients with frequent blood transfusion, moderate to high Medication Complexity Index (MRCI) and of Malay ethnicity were associated with higher odds of having a DRP (AOR 4.09, 95% CI: 1.83, 9.15; AOR 4.50, 95% CI: 1.89, 10.75; and AOR 3.26, 95% CI: 1.43, 7.43, respectively). Conclusion: The prevalence of DRP was relatively high amongst TDT patients. Increased medication complexity, more severe form of the disease and Malay patients were more likely to experience DRP. Hence, more viable interventions targeted to these groups of patients should be undertaken to mitigate the risk of DRP and achieve better treatment outcomes.